1976
DOI: 10.1007/bf00561495
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and immunology of the Henoch-Sch�nlein-syndrome

Abstract: The Henoch-Schönlein-syndrome, or anaphylactoid purpura, is usually a childhood disease. The progess of this syndrome in adults was observed in 4 cases at our clinic. An elevated IgA level in the serum with a normal complement value seems to be of immunological interest. By immunohistological methods fibrin and IgA could be demonstrated in skin and kidney biopsies; in glomerulae C3c was observed, occasionally accompanied by Properdin-factor-B. These findings differentiate this disease from other allergic super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The perivascular or diffuse deposition of fibrin and fibrinogen have already been described (2,17). Vascular and perivascular deposits of plasminogen in the skin of Schonlein-Henoch-purpura are reported for the first time in this paper.…”
Section: Discussionsupporting
confidence: 62%
“…The perivascular or diffuse deposition of fibrin and fibrinogen have already been described (2,17). Vascular and perivascular deposits of plasminogen in the skin of Schonlein-Henoch-purpura are reported for the first time in this paper.…”
Section: Discussionsupporting
confidence: 62%
“…Despite the presence of C3 and properdin on immunohistological examination of renal biopsy material from patients with HSP nephritis [7,8], and the demonstrated deposition of the MAC in the vessel walls of skin lesions [13,14] and the capillary walls and mesangium of glomeruli [12,13], serological evidence of complement activation has not been a consistent finding in clinical studies. Garcia-Fuentes et al [9] studied 23 children with acute HSP and found a low CH50 in 9, low serum properdin in 5, but normal levels of serum C1q, C4 and C3.…”
Section: Discussionmentioning
confidence: 99%
“…HSP has been associated with C2 deficiency [4] homozygous null C4 phenotypes [5] and C4B deficiency [6]. C3 and properdin are seen in glomerular immunohistology [7,8] and studies of patients with acute HSP have demonstrated low CH50, low serum properdin [9] and raised serum C3d levels [10,11], each of which returned to normal as the disease resolved. The membrane atack complex, C5b-9 (MAC), has also been demonstrated in skin and renal biopsies [12 -14] and studies in adult patients with HSP have shown increased serum levels of the MAC [14].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of H-S disease remains unknown but IgA-containing immune complexes might be involved in the development of tissue lesions according to the following observations: (1) several authors (2, 3,4, 5) have demonstrated circulating IgA-containing immune complexes in this disease; (2) we have observed increased plasma levels of IgA and CIC during the acute phase in most children and in patients presenting persistent urinary signs after the acute phase; (3) IgA has been found in the glomerular mesangium (6, 7) and in cutaneous lesions (7); (4) we have shown an activation of the complement system during acute phases. This activation probably involves the alternative pathway since immunofluorescence studies have demonstrated the presence of properdin and C3, but not of ClQ or C4 in the mesangium (7,8); (5) Emancipator et al (21) have recently described an experimental model of IgA-nephropathy induced by oral immunization of mice with various exogenous proteins.…”
Section: Discussionmentioning
confidence: 99%